Triglyceride-glucose-body mass index predicts early-onset acute kidney injury in critically ill patients: a retrospective analysis using the MIMIC-IV database - Zhu, Qiang; Zong, Qunchuan; Guo, Shiying; Ma, Yonghong; Zhang, Miao; Jin, Ningjing; Ba, Yinggui; Zou, Huajie; Zhang, Ruixia (Frontiers in Nutrition, 2026)
BackgroundAcute kidney injury (AKI) is a common and serious complication in critically ill patients, with metabolic dysfunction playing a crucial role in its pathogenesis. The triglyceride-glucose-body mass index (TyG-BMI) has emerged as a novel marker of insulin resistance and metabolic health. However, the relationship between TyG-BMI and early-onset AKI in critically ill patients remains unclear. The aim of this study was to evaluate the association between TyG-BMI and early-onset AKI in critically ill patients, and identify optimal cutoff thresholds for risk stratification.MethodsThis retrospective study analyzed 4,024 critically ill adults from the MIMIC-IV database. Patients were stratified according to TyG-BMI quartiles. Cox proportional hazards models, restricted cubic splines (RCS), and receiver operating characteristic (ROC) analyses were employed to examine associations between TyG-BMI and early-onset AKI. Optimal cutoff values were determined using the Youden index, while net reclassification improvement (NRI) assessed incremental predictive value.ResultsEarly-onset AKI developed in 2,535 patients (63.0%). Multivariable-adjusted hazard ratios increased across TyG-BMI quartiles, with the highest quartile showing significantly increased risk compared to the lowest (HR 1.40, 95% CI: 1.25–1.58). Risk increased approximately linearly when TyG-BMI exceeded 261.84. The optimal cutoff value was 252.50 (sensitivity 0.604, specificity 0.648). Adding TyG-BMI to traditional risk models improved prediction (NRI = 0.141, 95% CI: 0.024–0.207). Associations were stronger among males, younger patients, those with preserved eGFR, and patients with diabetes or sepsis.ConclusionTriglyceride-glucose-body mass index independently predicts early-onset AKI in critically ill patients. The threshold of 252.50 offers a reliable reference for risk stratification in ICU settings.